Extended therapy with letrozole as adjuvant treatment of postmenopausal patients with early-stage breast cancer: a multicentre, open-label, randomised, phase 3 trial. Issue 10 (October 2021) - Del Mastro, Lucia; Mansutti, Mauro; Bisagni, Giancarlo; Ponzone, Riccardo; Durando, Antonio; Amaducci, Laura; Campadelli, Enrico; Cognetti, Francesco; Frassoldati, Antonio; Michelotti, Andrea; Mura, Silvia; Urracci, Ylenia; et al.
Summary: Background: The benefit of extending aromatase inhibitor therapy beyond 5 years in the context of previous aromatase inhibitors remains controversial. We aimed to compare extended therapy with letrozole for 5 years versus the standard duration of 2–3 years of letrozole in postmenopausal patients with breast cancer who have already received 2–3 years of tamoxifen. Methods: This multicentre, open-label, randomised, phase 3 trial was done at 69 hospitals in Italy. Women were eligible if they were postmenopausal at the time of study entry, had stage I–III histologically proven and operable invasive hormone receptor-positive breast cancer, had received adjuvant tamoxifen therapy for at least 2 years but no longer than 3 years and 3 months, had no signs of disease recurrence, and had an Eastern Cooperative Oncology Group performance status of 2 or lower. Patients were randomly assigned (1:1) to receive 2–3 years (control group) or 5 years (extended group) of letrozole (2·5 mg orally once a day). Randomisation, with stratification by centre, with permuted blocks of size 12, was done with a centralised, interactive, internet-based system that randomly generated the treatment allocation. Participants and investigators were not masked to treatment assignment. The primary endpoint was invasive disease-free survival in the intention-to-treat population. Safety analysis was done for patients who received at least 1 month of study treatment. This trial was registered with EudraCT, 2005-001212-44, and ClinicalTrials.gov, NCT01064635 . Findings: Between Aug 1, 2005, and Oct 24, 2010, 2056 patients were enrolled and randomly assigned to receive letrozole for 2–3 years (n=1030; control group) or for 5 years (n=1026; extended group). After a median follow-up of 11·7 years (IQR 9·5–13·1), disease-free survival events occurred in 262 (25·4%) of 1030 patients in the control group and 212 (20·7%) of 1026 in the extended group. 12-year disease-free survival was 62% (95% CI 57–66) in the control group and 67% (62–71) in the extended group (hazard ratio 0·78, 95% CI 0·65–0·93; p=0·0064). The most common grade 3 and 4 adverse events were arthralgia (22 [2·2%] of 983 patients in the control group vs 29 [3·0%] of 977 in the extended group) and myalgia (seven [0·7%] vs nine [0·9%]). There were three (0·3%) serious treatment-related adverse events in the control group and eight (0·8%) in the extended group. No deaths related to toxic effects were observed. Interpretation: In postmenopausal patients with breast cancer who received 2–3 years of tamoxifen, extended treatment with 5 years of letrozole resulted in a significant improvement in disease-free survival compared with the standard 2–3 years of letrozole. Sequential endocrine therapy with tamoxifen for 2–3 years followed by letrozole for 5 years should be considered as one of the optimal standard endocrine treatments for postmenopausal patients with hormone receptor-positive breast cancer. Funding: Novartis and the Italian Ministry of Health. Translation: For the Italian translation of the abstract see Supplementary Materials section.